Beyond the Surface: The Peculiar World of Benthic Biodiversity, from Microbes to Multicellular Life and Their Ecosystem Roles - Mayya Gogina; Judith Piontek (Biology)
Below the water column depths, marine sediments harbor a vibrant tapestry of life that underpins a variety of ecological balances [...]